Sejarah dan Perkembangan MI Islamiyah Kroya Kecamatan Kroya Kabupaten Cilacap - Mar’ie Ahmad Syauqi (Progam Studi Sejarah Peradaban Islam (SPI), Fakultas Ushuluddin Adab dan Humaniora, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
This study examines the history and development of MI Islamiyah Kroya, Kroya District, Cilacap Regency. The method that will be used in this research is the historical research method because in the study it discusses the history and development of Madrasah Ibtidaiyah Islamiyyah Kroya to the local community. This research will be conducted through observation, interviews and document studies. The results of this study reveal that the early history of Madrasah Ibtidaiyah Islamiyah Kroya dates back to 1948, the year when the Dutch were forced to leave Indonesia by the Japanese army in 1942. Because they felt disturbed by their security in that year, some Kroya residents and religious leaders Islam left Kroya and moved to another area that he felt was safe. With such conditions, a figure in Kroya named Bpk. Dulah Hadwi, Naib at the Kroya District Marriage Office (KUA) tried to find protection to keep the Islamic fatwa up, and in this effort Mr. Dulah Hadwi accepted a business partner, namely Mr. R. Sapandi, Obseter (Kep. DPU) Kroya. His recommendation was to establish a Madrasah in Kauman Kroya, which is a school that specifically teaches Islamic religious lessons to minors with the desire to maintain the preservation of Islamic fatwas in Kroya while simultaneously educating the nation's youth in order to help the government and protect them from unwanted things from the Dutch.